2021
DOI: 10.3390/su13063131
|View full text |Cite
|
Sign up to set email alerts
|

New Coordinated Tuning of SVC and PSSs in Multimachine Power System Using Coyote Optimization Algorithm

Abstract: This paper presents a new approach for coordinated design of power system stabilizers (PSSs) and static VAR compensator (SVC)-based controller. For this purpose, the design problem is considered as an optimization problem whose decision variables are the controllers’ parameters. Due to nonlinearities of large, interconnected power systems, methods capable of handling any nonlinearity of power networks are mostly preferable. In this regard, a nonlinear time domain based objective function is used. Then, the coy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Most of this research has been focused on the coordinated design of SVC and PSS controllers. For coordinated design of power system controllers, a large number of such algorithms have recently been offered, including Teaching-Learning Algorithm (TLA) [15], Bacterial Foraging Optimization (BFO) [16], Brainstorm Optimization Algorithm (BOA) [17], Coyote Optimization Algorithm (COA) [18], ant colony optimization (ACO) [19], bat algorithm (BAT) [20], bee colony algorithm (BCA) [11], Genetic Algorithm (GA) [21], particle swarm optimization (PSO) [22], flower pollination algorithm (FPA) [23], gravitational search algorithm (GSA) [24,25], sine-cosine algorithm (SCA) [26], grey wolf optimizer (GWO) [27], firefly algorithm (FA) [28], Differential Evolution (DE) [29], Biogeography-Based Optimization (BBO) [30], Cuckoo Search (CS) algorithm [31], Harmony Search (HS) [32], Seeker Optimization Algorithm (SOA) [33], Imperialist Competitive Algorithm (ICA) [34], Harris Hawk Optimization (HHO) [35], Sperm Swarm Optimization (SSO) [36], Tabu Search (TS) [37], Simulated Annealing [38], Multi-Verse Optimizer (MVO) [39], Moth-Flame Optimization (MFO) [40], and collective decision optimization (CDO) [41]. Although metaheuristic algorithms could provide relatively satisfactory results, no algorithm could provide superior performance than others in solving all optimizing problems.…”
Section: Introductionmentioning
confidence: 99%
“…Most of this research has been focused on the coordinated design of SVC and PSS controllers. For coordinated design of power system controllers, a large number of such algorithms have recently been offered, including Teaching-Learning Algorithm (TLA) [15], Bacterial Foraging Optimization (BFO) [16], Brainstorm Optimization Algorithm (BOA) [17], Coyote Optimization Algorithm (COA) [18], ant colony optimization (ACO) [19], bat algorithm (BAT) [20], bee colony algorithm (BCA) [11], Genetic Algorithm (GA) [21], particle swarm optimization (PSO) [22], flower pollination algorithm (FPA) [23], gravitational search algorithm (GSA) [24,25], sine-cosine algorithm (SCA) [26], grey wolf optimizer (GWO) [27], firefly algorithm (FA) [28], Differential Evolution (DE) [29], Biogeography-Based Optimization (BBO) [30], Cuckoo Search (CS) algorithm [31], Harmony Search (HS) [32], Seeker Optimization Algorithm (SOA) [33], Imperialist Competitive Algorithm (ICA) [34], Harris Hawk Optimization (HHO) [35], Sperm Swarm Optimization (SSO) [36], Tabu Search (TS) [37], Simulated Annealing [38], Multi-Verse Optimizer (MVO) [39], Moth-Flame Optimization (MFO) [40], and collective decision optimization (CDO) [41]. Although metaheuristic algorithms could provide relatively satisfactory results, no algorithm could provide superior performance than others in solving all optimizing problems.…”
Section: Introductionmentioning
confidence: 99%
“…As per literature, recently the use of metaheuristic algorithms for the optimal tuning of lead–lag‐based PSS and coordination with a different type of FACTS is noteworthy. Numerous different metaheuristic algorithms are used like, particle swarm optimization, 5–7 genetic algorithms, 8,9 backtracking search algorithm, 10 Jaya algorithm, 11 gray wolf optimizer, 12 a hybridization of bat algorithm, gravitational search algorithm and particle swarm optimization are used in Reference 13, farmland fertility algorithm, 14 salp swarm algorithm, 15 kidney‐inspired algorithm, 16 whale optimization algorithm, 17 cuckoo search, 18 Henry gas solubility optimization, 19 collective decision optimization algorithm, 20 slime mold algorithm, 21 coyote optimization algorithm 22 …”
Section: Introductionmentioning
confidence: 99%
“…From the literature review, it was found that several ideas and methods have been suggested for the optimal setting of PSS parameters. The most used PSS design methods are summarized in [9][10] and are divided into three main categories which are adaptive control [11][12], linear approximation [13], and nonlinear models [14]. In [12], Model Reference Adaptive System-based PSS (MRAS-PSS) design has been addressed.…”
Section: Introductionmentioning
confidence: 99%